Primary renal carcinoid: Treatment and prognosis - (:unkn) unknown (ELSEVIER SCIENCE INC, 2013)
Primary carcinoid tumors of the kidney are very rare, malignant tumors consisting of neuroendocrine cells. The pathogenesis of renal carcinoid is unclear because neuroendocrine cells are not normally found in adult renal parenchyma. Electron microscopy, immunohistochemistry, octreotide scan, positron emission tomography along with conventional radiographic imaging techniques are used in diagnosis and follow-up. Presenting symptoms usually include flank pain and haematuria. Early stage disease is treated with surgery only. However, randomized trials are lacking because of the very low number of reported cases. Thus, the role of debulking surgery, chemotherapy, radiotherapy, octreotide and targeted therapy in the management of advanced disease remains an open question. In this article the clinicopathologic features and prognosis of this very rare disease along with treatment outcomes of the reported cases are reviewed. In addition, we report a new case of a metastatic primary renal atypical carcinoid tumor treated with octreotide therapy. (c) 2013 Elsevier Ireland Ltd. All rights reserved.
Keywords: Primary renal carcinoid; Neuroendocrine tumors; Octreotid; Prognosis; HORSESHOE KIDNEY; MATURE TERATOMA; NEUROENDOCRINE TUMORS; ENDOCRINE TUMOR; CYSTIC TERATOMA; PELVIS